Farmers’ Attitude to Improved Soil and Water Conservation Practices in the Environs of Simen Mountains National Park, Ethiopia - Girmachew Siraw, (Journal of Agricultural Extension Management, 2025)
In the past, many soil and water conservation practices were introduced in Ethiopia. However, those technologies failed to win acceptance of the land users because of their limitations and constraints. Thu s, identification of constraints in relation to the adoption of soil and water conservation practices is of paramount importance. A study was undertaken in the environs of Si men Mountain National Park area of Amhara state to assess farmers' attitude on the existing soil erosion and soil and water conservation and to identify alternative approaches and strategies to promote improved soil and water conservation technologies. The results of the study show that farmers' level of perception on soil erosion and soil and water conservation is significantly related to adoption of soil and water conservation practices by the farmers. Incorporating farmers ' views in the design of physical works undertaken in soil and water conservation should be practiced as an alternative policy and strategy to promote improved soil and water conservation practices.